Fish and trophic connectivity across coral reef and mangrove habitats of north eastern Langkawi Island, Peninsular Malaysia / Lau Chai Ming - Lau, Chai Ming (2014)
The presence of disparate biotopes of coral reefs and mangroves in one general area is unique. These biotopes may form ecologically connected ecosystems when occurring in close proximity such as in tropical Langkawi Island, Malaysia. Connected marine biotopes can provide various ecological services to fish community such as nursery, feeding habitats and shelter. As such, this study aims to test two hypotheses regarding Langkawi’s coral reefs and mangroves 1) the biotopes are ecologically connected via habitat utilization by the fish fauna and 2) the biotopes are ecologically connected via trophic energy pathways. Gill nets and fish pots were deployed to determine common overlapping fish species in both biotopes. Samples of primary producers, sediment and consumers were subjected to dual stable isotope analysis and stomach content analysis in the case of fishes. Coral community and habitat complexity as proxies for refuge cover were determined based on r-K-S adaptive strategists and coral morphology diversity respectively. The present study discovered a relatively high number of common species, 31 out of a total of 149 fish species, suggested there was movement of fishes between habitats. Despite the turbid water, the coral cover was considerably high, 47.21% with low mortality and dominated by stress-tolerators. The habitat complexity was also relatively high with 2.06 index of morphological diversity indicated a fairly good refuge area. Stomach content analysis of fish revealed benthic invertebrates and small nekton as the main food items. Stable isotope analysis showed that the δ13C values of zooplankton (-21.66 ± 0.72 ‰ SE) were closer to phytoplankton (-21.64 ± 0.79 ‰ SE). The fishes even as far as the upstream mangrove had relatively enriched δ13C values (-8.88 to -22.37 ‰) close to the values of coral zooxanthellae (-15.39 ± 0.33 ‰ SE) and phytoplankton, but distinctly distant from mangrove-derived source (-28.83 ± 0.38 ‰ SE). A Bayesian mixing model of stable isotopic analysis in R (SIAR) depicted coral zooxanthellae as the major carbon contributor to fish nutrition in the coral reefs (90.0%) and mangrove (63.7%). Since phytoplankton contributed 32.0% in the mangrove estuary, mangrove carbon was relatively unimportant to the food web even in the mangrove estuary itself. Under the turbid water condition, mucus productions are expected by corals. It is hypothesized that coral mucus and zooplankton are the vehicles of energy transfer from coral zooxanthellae to consumers in the mangrove habitat. The present study suggests that fish movements and outwelling of extruded mucus and zooplankton connect coral reef to mangrove.